Hubungan Riwayat Paparan Pestisida Dengan Profil Darah Pada Wanita Usia Subur di Daerah Pertanian Cabai Dan Bawang Merah - Dwi Marinajati; Nur Endah Wahyuningsih; suhartono suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Pesticides use is known to cause serious health impact ob human, one of them is abnormalities of blood profile. District of Brebes is one of the largest consumers of pesticides in Indonesia which correlate with its high production on chili and shallot. Most women of childbearing age in this area ara involved in farming which make them having great risk to have abnormalities of blood profile. The study conducted to search relation between pesticides exposure and blood profile on women child bearing age in agriculture area. Method : This was a cross-sectional study involving 80 women of childbearing age lived in agriculture area. Result : Involvement in agricultural activities (p=0,023, RP=1,52, 95%CI =1,00 to 2,29), pesticides exposure (p=0,007, RP=1,98, 95%CI=1,00 to 3,89), looking for pest (p=0,004, RP=1,52, 95% CI=1,12 to 2,04), harvesting (p=0,001, RP=1,69, 95% CI =0,19 to 2,39), releasing shallot from the stem (p=0,008, RP=1,44); 95%CI = 1.13 to 1,84) associated with increased of monocytes differential count. The result of logistic regression analysis showed pesticides exposure associated with increased of monocytes differential count (p=0,004, RP=7,50, 95% CI=1,92 to 29,29). Conclusion of the findings showed relation between pesticides exposure and increased of monocytes differential count. The finding of this study can be used for information dissemination and pesticide reduction programs in agriculture area. Keywords: women of childbearing age, pesticide, chili, shallot and blood profile